1969
DOI: 10.1126/science.164.3879.566
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Sensitive Adenyl Cyclase in Plasma Membrane of Hepatic Parenchymal Cells

Abstract: The plasma membrane of hepatic parenchymal cells contains an adenyl cyclase system that is stimulated by glucagon. Adrenocorticotropin and epinephrine do not stimulate this adenyl cyclase, and very little cyclic phospho-diesterase activity is present in the membrane. These findings support the concept that glucagon exerts its regulatory action in the liver by stimulating adenyl cyclase activity in the plasma membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
63
0
1

Year Published

1970
1970
1996
1996

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(66 citation statements)
references
References 12 publications
2
63
0
1
Order By: Relevance
“…Although Pohl et al [12] have demonstrated a hormone sensitive adenyl cyclase of high specific activity in the plasma membrane of rat liver, it is not known whether there are other subcellular components with adenyl cyclase activity in this organ. The particle preparation employed in the present work was therefore chosen to comprise most of the particulate material of the liver after washing away the soluble protein which contains most of the phosphodiesterase activity [14].…”
Section: Studies On the Assay Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Although Pohl et al [12] have demonstrated a hormone sensitive adenyl cyclase of high specific activity in the plasma membrane of rat liver, it is not known whether there are other subcellular components with adenyl cyclase activity in this organ. The particle preparation employed in the present work was therefore chosen to comprise most of the particulate material of the liver after washing away the soluble protein which contains most of the phosphodiesterase activity [14].…”
Section: Studies On the Assay Systemmentioning
confidence: 99%
“…I n order to prevent breakdown of labeled Ado-3':5'-P in the reaction, theophylline, or the better soluble aminophylline were added to the incubation system at concentrations of 10 and 20 mM, respectively. However, further experiments which included high concentrations of unlabeled Ado-3' : 5'-P in the assay system [15], revealed that both methyl xanthines were either inhibiting the adenyl cyclase (see also [12]) or not completely blocking phosphodiesterase activity in the present system. Thus, as derived from Fig.1, 10 mM Ado-3' : 5'-P seemed the appropriate concentration and was routinely used in the test.…”
Section: Studies On the Assay Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Epididymal fat pads from 3 T-KK or 4 control mice were combined to prepare a single batch of fat cell ghosts. Adenyl cyclase was measured as described by Pohl, Birnbaumer and Rodbell [12] from the rate of formation of cyclic AMP from ATPa~P. The reaction mixture contained final concentrations 3.2 mM Tris-ATP, 5 mM MgCl~, 25 mM Tris-HC1 (ptI 7.4), 10 mM theo- was added to 0.80 ml of a 50% settled volume of BioRad AG-IX, 2--400 mesh, which was previously packed in a column, washed with 1 N Na0H, repeatedly with water, with 1 N HCI and finally with water to neutrality.…”
Section: Preparation Of Fat Cell Ghosts and Measurement Of Adenyl Cyementioning
confidence: 99%
“…The localization of adenyl cyclase in the plasma membrane of liver and the stimulation of the membrane bound adenyl cyclase by glucagon or epinephrine have been reported (Marinetti et al, 1969;Pohl et al, 1969 and dried, was dissolved in a 10ml of Bray's scintillator (Bray, 1960 shown in Figure 4. The glucagon stimulated adenyl cyclase activity was markedly inhibited Fig.…”
mentioning
confidence: 99%